2021
DOI: 10.3390/vaccines9111359
|View full text |Cite
|
Sign up to set email alerts
|

Compliance Indicators of COVID-19 Prevention and Vaccines Hesitancy in Kenya: A Random-Effects Endogenous Probit Model

Abstract: Vaccine hesitancy remains a major public health concern in the effort towards addressing the COVID-19 pandemic. This study analyzed the effects of indicators of compliance with preventive practices on the willingness to take COVID-19 vaccines in Kenya. The data were from the COVID-19 Rapid Response Phone Surveys conducted between January and June 2021 during the fourth and fifth waves. The data were analyzed with the random-effects endogenous Probit regression model, with estimated parameters tested for robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
(88 reference statements)
1
8
0
3
Order By: Relevance
“…It was clear from our study that our respondents’ risk perception was related to their attitude about that vaccine. Similar to other studies, our study showed that higher levels of education and increasing age were associated with getting a COVID-19 vaccine [ 44 , 45 , 46 , 47 ]. This is contrary to what the Africa CDC found in its study reporting that people with primary level education and less were more likely to show confidence in the importance and safety of the vaccine, but they also reported that older people were more likely to get the COVID-19 vaccine; 20% of Kenyans aged 18–24 were not willing to take the vaccine versus 7% over the age of 55 [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…It was clear from our study that our respondents’ risk perception was related to their attitude about that vaccine. Similar to other studies, our study showed that higher levels of education and increasing age were associated with getting a COVID-19 vaccine [ 44 , 45 , 46 , 47 ]. This is contrary to what the Africa CDC found in its study reporting that people with primary level education and less were more likely to show confidence in the importance and safety of the vaccine, but they also reported that older people were more likely to get the COVID-19 vaccine; 20% of Kenyans aged 18–24 were not willing to take the vaccine versus 7% over the age of 55 [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…Being male was the most commonly reported factor associated with increased acceptability of the COVID-19 vaccine [ 21 28 ]. Other factors that were associated with COVID-19 vaccine acceptance included higher level of education [ 21 , 25 , 28 34 ], working in a health-related occupation especially as a medical doctor [ 26 , 35 ], greater knowledge of COVID-19 or fear of contracting the virus (including having flu-like symptoms, being tested for COVID-19, or relatives who had contracted the virus) [ 36 39 ]. Also, possessing positive perceptions towards vaccine sources and the pharmaceutical industry [ 40 ] and higher income [ 39 ] were reported as facilitators of vaccine acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for vaccine hesitancy varied across studies (Table 2 ). Concern for safety was the most-mentioned factor [ 17 19 , 25 , 34 , 36 , 36 , 37 , 37 , 38 , 40 , 41 , 41 43 , 43 53 ]. Some of these concerns appeared to stem from mistrust towards the pharmaceutical industry, results from clinical trials, poor vaccine promotion with conflicting information, misinformation from social media, and the fear of getting ill or side effects from the vaccine [ 26 , 36 , 40 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Impfbereitschaft [ 24 , 25 , 31 , 32 ]. Weitere in mehreren Studien als Risikofaktoren für Nichtimpfung genannte Aspekte waren ein junges Alter [ 21 , 23 , 32 35 ], Fehlen eines festen Wohnsitzes [ 23 , 29 ], ein geringes Bildungsniveau [ 18 , 33 , 35 , 36 ], allgemein soziale Benachteiligung bzw. ein niedrigerer sozioökonomischer Status [ 6 , 26 , 29 ] sowie als weiterer Aspekt eine (stationäre) Behandlung gegen den Willen der Betroffenen [ 16 , 21 ].…”
Section: Diskussionunclassified